RARE-01. ASSESSING THE SYMPTOM DIAGNOSTIC INTERVAL FOR CHILDREN WITH CENTRAL NERVOUS SYSTEM TUMOURS. (1st June 2021) - Crowell, Cameron; Crooks, Bruce; Walling, Simon; Boileau, Kelly; Bowes, Lynette; Rutledge, Robert; Kulkarni, Ketan; McNeely, Daniel; Erker, Craig
Abstract: Background: Diagnostic delays in pediatric neuro-oncology is a subject of distress for families and providers. We aimed to evaluate the symptom diagnostic interval (SDI) and influencing variables for children with CNS tumors. Methods: This retrospective study analyzed 210 patients diagnosed from 2001–2018 and managed at the tertiary care facility in Halifax, Canada. SDI was defined as time from first symptom until tissue diagnosis or, if not available, imaging diagnosis. Non-parametric tests were used to compare SDI between groups. Results: Median SDI was 12.4 weeks (IQR 4.3–30), longer than 7 other studies of 1308 children reporting medians of 4.5–10 weeks ( p < 0.01). Most common tumors and their median SDI included low-grade glioma (LGG) (n=97, 46%; 17.9 weeks), medulloblastoma (n=31, 15%; 8.7 weeks), high-grade glioma (HGG) and DIPG (n=23, 11%; 5.6 weeks), and ependymoma (n=13, 6%; 13.6 weeks). The most common initial reported symptom included headache (n=63; 30%), nausea/vomiting (n=27, 18%), seizure (n=24, 12%), and visual impairment (n=13, 6.3%). Patients aged 0–3 years had a shorter SDI than patients 10 years and older (SDI 8.7 vs 14.6 weeks; p = 0.03). Tumor category showed longer SDI for LGG versus HGG ( p = 0.003), DIPG ( p = 0.02), medulloblastoma ( p = 0.03) and other embryonal tumors ( p = 0.03). Longer SDI was not associated with increased risk of disease progression for LGG ( p = 0.93), medulloblastoma ( p = 0.89), or ependymoma ( p = 0.5). No difference in SDI was found with regard to diagnosis era, ethnicity, socioeconomic status, or distance to the tertiary care facility. Conclusion: SDI at our centre is longer than previously reported studies. SDI is linked to tumor biology and its relevance within specific tumor groups deserves further investigation given it doesn't appear to predict tumor progression/recurrence, yet families and providers feel distress when delays in diagnosis are perceived.